Rękopis „Kartoteki” - Solski, Zbigniew Władysław (Wydawnictwo Naukowe UAM, 2009)
At the beginning of the 70s Tadeusz Różewicz presented the manuscript of Card Index to Professor Józef Kelera. It might have stayed a secret of friendship of the dramatist and the critic, however, Różewicz revealed the initials of his friend when in a commenatry to the play, he posed a question, whether there was a full stop after the last word in the manuscript or not? Posing this question, the author claimed the integrality of his masterpiece which was threatened by the widespread interpretations of Card Index as a play of a loose and dispersed structure. Appreciating the value of this question, I turned to Professor Kelera. This way I have had an access to the autograph of the play. In this manuscript has been preserved the play from before its final editing, which its author must surely have made during typing the text. Handwritten notes contain two unknown versions of the play with fragments which would not have been passed by the censors in the then Polish People’s Republic. In the reading of the manuscript the functions of the word and its graphic shape appeared of equal importance, so this version of Card Index can be recognised as a masterpiece of literature.
The manuscript of Kartoteka (Card Index)